Association of the In Vitro Susceptibility of Clinical Isolates of Chlamydia trachomatis With Serovar and Duration of Antibiotic Exposure. Issue 3 (March 2015) - Zheng, Heping; Xue, Yaohua; Bai, Shun; Qin, Xiaolin; Lu, Ping; Yang, Bin
Abstract : Background: The presence of persistent Chlamydia trachomatis infection after treatment does not always correlate with in vitro susceptibility testing. Methods: The in vitro minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of azithromycin, clarithromycin, roxithromycin, doxycycline, tetracycline, ofloxacin, and penicillin were tested against 61 clinical isolates of C. trachomatis on 6 serovars, and the MIC/MBC of azithromycin and ofloxacin at different points in time after antibiotic administration to infected cultures. Results: Of the 7 antibiotics tested, clarithromycin showed the greatest activity against C. trachomatis isolates with MIC90 of 0.032 μg/mL and MBC90 of 0.064 μg/mL, followed by doxycycline with MIC90 0.064 μg/mL and MBC90 0.064 μg/mL, and azithromycin with MIC90 0.160 μg/mL and MBC90 0.320 μg/mL. Azithromycin had roughly the same MIC50 values (0.08 μg/mL) as the other serovars isolates tested, and other antibiotics showed a 2- to 4-fold difference in MICs50 between serovars. In addition, an increase in the azithromyin MIC was observed by 8 hours and the ofloxacin MIC by 16 hours. At 24 hours, the azithromycin MICs were greater than 40 μg/mL and ofloxacin MICs were greater than 64 μg/mL. Conclusions: The current data demonstrated that the antimicrobial susceptibility of C. trachomatis was influenced by both the serovar type and the duration of exposure to antibiotics in infected cultures. Abstract : Our in vitro findings confirmed that clarithromycin, doxycycline, and azithromycin are more effective than other antibiotics at reducing the number of Chlamydia trachomatis infections. The current data also indicated that the serovar of C. trachomatis and the addition time of the antibiotics were the influencing factors of antibiotic against C. trachomatis .